An ecological psychology perspective in teaching Chinese online - Paul Jing; Nuesser Michaela; Zheng Dongping (Journal of China Computer-Assisted Language Learning)
In this paper, we first introduce three ecological principles for designing Chinese language online teaching and learning activities drawing from ecological psychology. The first principle – perception and action cycles in an ecosystem, advocates for situating online learning in a physical environment and creates activities with potentials to engage perception-action cycles. With the second principle – intention and attention merge in an ecosystem, we advocate for designing complex, flexible and dynamic activities and providing scaffolding for attunement. The third – meaning-making and values-realizing coincide in an ecosystem, calls for designing activities that allow for care-taking of oneself, each other, and the environment and cultivate curiosity and mindfulness for values-realizing and individual meaning-making. To highlight ways to tap into learners’ interest and connect to people and places, we then share two example activities with both low-technology and high-technology options.